Theoretical studies of the steering hydraulic system of construction and road machines with flow amplifiers - A. V. Zhdanov (Омский научный вестник)
The article presents the results of theoretical studies of the functioning of flow amplifiers, the purpose of which is to increase the useful power of the hydraulic steering systems of heavy construction and road machines, which is especially important when upgrading existing equipment and designing a new one. Flow amplifiers allow to increase the supply of working fluid to the hydraulic cylinders for turning a multiple of the dosed volume by the dosing pump. A distinctive feature of the study is the consideration of two flow amplifiers of throttling and volumetric types, working in pairs. The design, the principle of operation are described, the main calculated dependencies are presented, on the basis of which mathematical modeling was carried out. To evaluate the qualitative and quantitative characteristics of the amplifiers, graphs of transient processes in the steering hydraulic system, as well as the static characteristics of the flow amplifiers, were obtained. The analysis of the obtained dependencies showed acceptable accuracy and quality of the hydraulic system. The results obtained can be used in the synthesis of such systems.